Handling of Corruption Crimes at the Tanggahan Peken Village Credit Institution, Susut District, Bangli Regency Handled by the Bali Police - Ananta Putra Komang; Nurianto RS; I Nyoman Suandika (Journal of Social Research, 2024)
Lembaga Perkreditan Desa (LPD) is a vital financial institution for traditional villages in Bali, whose role is to save funds, provide credit, and support village development. However, some LPDs, such as Tanggahan Peken LPD in Bangli Regency, have experienced legal problems related to alleged corruption crimes committed by their administrators. The purpose of this study is to determine and analyze the handling of criminal acts at the Tanggahan Peken Village Credit Institution, Susut District, Bangli Regency handled by the Bali Police. The natural method of this research uses empirical legal research. The results showed that the occurrence of criminal acts of corruption committed by the Tanggahan Peken LPD management was caused by internal factors from the individual aspect of the LPD management to gain profit, enrich themselves and perpetuate their positions and external factors from the organizational aspect, namely the lack of regular guidance, supervision and audits carried out by LPD internal supervisors and LPLPD as technical supervisors and audits. The handling of corruption crimes by the Bali Police at the Tanggahan Peken Village Credit Institution (LPD) uses Standard Operating Procedures (SOP) from the process of receiving public complaints, investigating and investigating. Creating effective investigation and investigation plans. Investigators also conduct independent audits and examinations by involving experts in the field of accounting and auditing, experts in the field of economics and experts in criminal law.